Analysis of the longitudinality attribute with the implementation of the advanced access model: multiple case study (Revista Contexto & Saúde, 2025)
The aim was to evaluate the longitudinality of care in family health units before, during, and after the implementation of the Advanced Access model. The reference for this evaluation was the usual provider continuity index (UPC). This was a descriptive study with a mixed-methods approach, conducted at the Southern Regional Coordination of the city of São Paulo-SP. The research participants were the coordinators of 5 basic health units (BHU), doctors, nurses, and 295 users of these BHU. Data were collected using the Primary Care Assessment Tool (PCATool) and production records available at the BHU. The data were organized on the REDCap® platform. Statistical analysis was performed using R® software. The results demonstrate that 3 of the 5 BHUs had a higher provider continuity index (UPC) before the implementation of the Advanced Access model, indicating that in these BHUs the implementation of the Advanced Access model compromised the longitudinality of care. In contrast, in two BHUs, there was an improvement in the provider continuity index (UPC) after the model was implemented. It was concluded that the longitudinality of care attribute was due to planning and coverage problems in the BHUs in the southern region of the city of São Paulo. These problems cannot be attributed solely to the implementation of the Advanced Access model.
Keywords: Longitudinality; Continuity of Patient Care; Access to Health Services; Primary Health Care; Accessible Primary Care